1996
DOI: 10.1021/es960409h
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of TNT by Aquatic Plants and Plant Tissue Cultures

Abstract: The ability of plants to uptake and transform 2,4,6-trinitrotoluene (TNT) was investigated using the aquatic plant Myriophyllum spicatum, axenic Myriophyllum aquaticum, and Catharanthus roseus hairy root cultures. Studies demonstrate that Myriophyllum, with or without its periphyton, and C. roseus transform TNT. Low concentrations of aminated nitrotoluenes (2-amino-4,6-dinitrotoluene and 4-amino-2,6-dinitrotoluene) were observed in the extracellular medium and tissue extracts. Primary products of transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
184
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(193 citation statements)
references
References 14 publications
6
184
3
Order By: Relevance
“…Currently, the use of aquatic macrophytes is under investigation as a viable alternative for remediation of a wide range of contaminants including heavy metals (Hughes et al, 1996;Lee et al, 1998;Rodgers and Bunce, 2001;Miglioranza et al, 2004;Miretzky et al, 2004;Polomski et al, 2009;Augustynowicz et al, 2010;Rahman and Hasegawa, 2011). These researches emphasize that the plant-based approach to remediation of the environments highly contaminated has an interesting cost-effective, because it is cheaper than other methods and safe for human.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the use of aquatic macrophytes is under investigation as a viable alternative for remediation of a wide range of contaminants including heavy metals (Hughes et al, 1996;Lee et al, 1998;Rodgers and Bunce, 2001;Miglioranza et al, 2004;Miretzky et al, 2004;Polomski et al, 2009;Augustynowicz et al, 2010;Rahman and Hasegawa, 2011). These researches emphasize that the plant-based approach to remediation of the environments highly contaminated has an interesting cost-effective, because it is cheaper than other methods and safe for human.…”
Section: Discussionmentioning
confidence: 99%
“…Plants have been shown to take up and, in some cases, to metabolize organic pollutants (6), excess nutrients (6, 7), 2,4,6-trinitrotoluene (TNT) (8,9), and metals (10,11). Work in our laboratory has demonstrated that poplar trees are able to take up and metabolize TCE both under laboratory conditions and in a field test (12)(13)(14).…”
mentioning
confidence: 89%
“…GSTs are enzymes known to be involved in the transformation of a large variety of toxic chemicals (Pflugmacher et al, 2000;Schroder et al, 2001;Maars, 1996;Edwards and Dixon, 2004), and they also are suspected to be (at least partially) responsible for the detoxification of TNT (Hughes et al, 1997;Bhadra et al, 1999). Even thought no direct evidence of such a mechanism has been obtained, we showed here that a purified, commercially-available GST was able to catalyze in vitro the conjugation of TNT with GSH.…”
Section: Discussionmentioning
confidence: 99%
“…A few transformation products have been identified, predominantly amino-and diamino-nitrotoluenes, (Harvey et al, 1990;Hughes et al, 1997;Thompson et al, 1998b;Larson et al, 1999), but incomplete information is available about the metabolism of TNT inside plant tissues.…”
Section: Introductionmentioning
confidence: 99%